Bangladeshi immigrants' willingness to report crime in New York City. (17th February 2017) - Khondaker, Mahfuzul I.; Wu, Yuning; Lambert, Eric G.
Abstract : Crime reporting by citizens has important implications for police effectiveness in crime control and community safety, yet research on immigrants' willingness to report crime to the police is very limited. Relying on a purposive and convenience sample of 202 Bangladeshi immigrants from six areas in the New York City, this study examined Bangladeshi immigrants' willingness to report crime and factors that may affect Bangladeshi immigrants' willingness to report crime. Results showed that a great majority of the participants reported that they were willing to report crime to the police, and there was a high level of concordance between the participants' crime-reporting intentions and behaviours. Both fear of crime and general satisfaction with the police were positively related to the Bangladeshi immigrants' willingness to report crime.